Perspectives of the public dental workforce on the dental management of people with special needs. (19th March 2021) - Lim, MAWT; Liberali, SAC; Calache, H; Parashos, P; Borromeo, GL
Abstract: Background: People with special health care needs continue to have difficulties accessing regular dental care partly due to oral health professionals feeling they lack the knowledge and experience to provide treatment to these individuals. Methods: Qualitative interviews and focus groups provided an insight into the types and nature of supports that oral health professionals working in the Australian public dental system desired and felt may improve their willingness and/or ability to treat patients with special needs. Results: Although participants did not identify one group of patients with special needs that were more difficult to treat, they did report a feeling of being unsupported. Clinicians felt that improved training and access to ongoing education in Special Needs Dentistry, opportunities for greater support from specialists or other health professionals, either through networking or other media such as telehealth, and fostering a more supportive clinical environment, particularly in relation to appointment lengths and productivity pressures, may improve their willingness and ability to treat patients with special needs. Conclusions: Additional support, in the form of greater interaction with specialists and reduced time and productivity pressures, may improve the willingness of oral health professionals in the public dental system to treat patients with special needs.